2012
DOI: 10.1002/art.34607
|View full text |Cite
|
Sign up to set email alerts
|

Role of plasma kallikrein–kinin system activation in synovial recruitment of endothelial progenitor cells in experimental arthritis

Abstract: OBJECTIVE This study aimed at determining whether activation of the plasma kallikrein‐kinin system (KKS) mediates synovial recruitment of endothelial progenitor cells (EPCs) in arthritis. METHODS EPCs were isolated from Lewis rat bone marrow, and expression of progenitor cell‐lineage markers and functional properties were characterized. EPCs were injected intravenously into Lewis rats with arthritis, and their recruitment and formation of de novo blood vessels in inflamed synovium were evaluated. The role of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…25,26 Plasma kallikrein B1 stimulates the recruitment of EPCs in inflamed tissue by bradykinin-mediated up-regulation of chemokine receptor type-4. 27 Hence, the combination of these proangiogenic and EPC-activating factors may have further contributed to the higher numbers of EPCs in endometriotic lesions of estrogen-stimulated mice.…”
Section: Epcs In Endometriosismentioning
confidence: 99%
“…25,26 Plasma kallikrein B1 stimulates the recruitment of EPCs in inflamed tissue by bradykinin-mediated up-regulation of chemokine receptor type-4. 27 Hence, the combination of these proangiogenic and EPC-activating factors may have further contributed to the higher numbers of EPCs in endometriotic lesions of estrogen-stimulated mice.…”
Section: Epcs In Endometriosismentioning
confidence: 99%
“…Although these experimental and clinical observations demonstrate that the KKS plays a critical role in the pathogenesis of arthritis, the molecular and cellular mechanisms by which the activation of the KKS mediates arthritis remains unknown. Recently we report that the inhibition of plasma kallikrein ameliorates arthritis in two Lewis rat models, PG-PS model and collagen-induced arthritis model, the effect of plasma kallikrein is probably through bradykinin [ 51 ]. Bradykinin has two receptors, constitutively expressed B2R and inducible B1R both belong to G protein-coupled receptors.…”
Section: Contact System In Inflammationmentioning
confidence: 99%
“…Recently, we have demonstrated that HKa regulates EPC functions in vitro [ 58 , 59 ], revealing the connection between the KKS activation and EPC biology. In rodent model of arthritis, we found another role of the KKS in the homing function of EPCs in arthritis [ 51 ]. In Lewis rat model of arthritis, EPCs are recruited to inflamed synovium and form new vessels, which was blocked by specific plasma kallikrein inhibitor; Bradykinin stimulates transendothelial migration of EPCs by selectively upregulating expression of homing receptor C-X-C motif receptor 4 (CXCR4) [ 51 ].…”
Section: Contact System In Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described, whole blood was collected by cardiac puncture. Immediately after separation of plasma by centrifugation, the levels of BK were measured ( Dai et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%